PERANCANGAN SINGKAWANG ART CENTER DENGAN PENDEKATAN ARSITEKTUR KONTEMPORER - Kurniansyah, Fajri; Alhamdani, Muhammad Ridha; Muazir, Syaiful (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2024)
Art is an individual, collective or communal artistic expression based on cultural heritage or the creativity of new creations, which are manifested in various forms of activity and media. Arts include performing arts, visual arts, literary arts, film and media arts. According to the Singkawang City Cultural Sector Data Base, the art sector in Singkawang City has several problems, namely lack of creativity, so there is a recommendation in the form of holding training with the aim of increasing creativity in work. In 2020, the number of arts in Singkawang City is 79 arts with the most arts being dance and music. According to Snyder, Anthony (1985) The methods used in planning and designing start from the idea stage, followed by the theoretical study stage, data collection stage using primary and secondary data methods, analysis stage, synthesis stage, pre-design stage, and design stage. The Singkawang Art Center consists of 3 floors, there is a lobby located in the middle, then on the left side of the lobby th ere is a gallery area and on the right side is the theater area. The design of this building uses a contemporary architectural approach which can be seen from building elements such as the use of walls made of glass or creating voids covered by transparent roofs, has a transparent facade which gives an open impression and optimizes greening by planting trees regularly .